2023
DOI: 10.1038/s41409-023-01941-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for a severe disease course in children with SARS-COV-2 infection following hematopoietic cell transplantation in the pre-Omicron period: a prospective multinational Infectious Disease Working Party from the European Society for Blood and Marrow Transplantation group (EBMT) and the Spanish Group of Hematopoietic Stem Cell Transplantation (GETH) study

Abstract: Risk factors for severe SARS-Cov-2 infection course are poorly described in children following hematopoietic cell transplantation (HCT). In this international study, we analyzed factors associated with a severe course (intensive care unit (ICU) admission and/or mortality) in post-HCT children. Eighty-nine children (58% male; median age 9 years (min-max 1–18)) who received an allogeneic (85; 96%) or an autologous (4; 4%) HCT were reported from 28 centers (18 countries). Median time from HCT to SARS-Cov-2 infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…29 Overall organ impairment caused by treatment-related toxicities as well as comorbidities among HSCT recipients could be the causes for the survival difference between the healthy pediatric population versus pediatric HSCT recipients. 26,28 The clinical features of the patients with COVID were similar to other studies, fever being the most common clinical presentation followed by cough. Characteristics of the patients in our cohort in comparison to other pediatric studies are summarized in Table 5.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…29 Overall organ impairment caused by treatment-related toxicities as well as comorbidities among HSCT recipients could be the causes for the survival difference between the healthy pediatric population versus pediatric HSCT recipients. 26,28 The clinical features of the patients with COVID were similar to other studies, fever being the most common clinical presentation followed by cough. Characteristics of the patients in our cohort in comparison to other pediatric studies are summarized in Table 5.…”
Section: Discussionsupporting
confidence: 82%
“…25 The causes of this higher OS in pediatric HSCT recipients compared to adults are not well understood. The longer median time to COVID-19 infection (median 15 months) after HSCT in CIBMTR study including pediatric and young adult HSCT patients was suggested as one of the factors of the high survival in their cohort, 26 but we also found similar high survival rates in our cohort despite a shorter median time from HSCT to COVID infection (median 7 months). Age-related differences in immune function, expression and distribution of angiotensin-converting enzyme 2 receptor in pediatric population, which is a receptor used by the virus to gain entry into cells, endothelial and clotting function were suggested as other cause of better survival rates in children.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The course of disease is less severe in pediatric HCT recipients compared to adults. 16 Multicenter studies in children and young adults receiving HCT report a mortality rate of 6%-9% [24][25][26] (occasionally higher at 21%), 27 and ICU admission in 9%-26%. 24,26,28 Despite the relative "mildness" of disease, [24][25][26] unfavorable outcomes such as ICU admissions and death are substantially more frequent in immunocompromised children compared to those with intact immunity who experience mostly asymptomatic disease, rarely leading to ICU admission (<1%) and death (<0.1%).…”
Section: Hct Recipientsmentioning
confidence: 99%